Analysis of the relationship between Co-Created Value, Consciousness Value, Perceived Economic Value, and Customer Loyalty Layout - Soesanto, Soesanto (Tarjih : Agribusiness Development Journal, 2024)
This study examines the simultaneous impact of Co-creating Customer Value (CCV), Value Consciousness (VC), and Perceived Economic Value (PEV) on Customer Loyalty (CL) within the Service-Dominant Logic (SDL) framework, highlighting the importance of customer loyalty amidst intense business competition. This study aims to analyze the partial and simultaneous effects of co-created value, value consciousness, and perceived economic value on customer loyalty toward eco-friendly flavored products, while also examining whether environmentally conscious consumers are more responsive to these variables, offering strategic insights for enhancing customer loyalty. This study addresses a theoretical gap in the literature by exploring the individual dimensions of the three elements, which have only been examined separately in prior research. A survey-based quantitative approach was used, with 150 respondents from the retail sector analyzed through multiple linear regression. The results show that the three independent variables have a unidirectional relationship with the dependent variable CL, which is significant regarding zinc. It is concluded that CCV, VC, and PEV significantly affect CL in terms of zinc. Individually, PEV provides the highest number in its influence, followed by VC, while CCV, although small, can adjust in the influence of combination. These findings support the concept of value-in-context, affirming that interaction value, benefit awareness, and economic perception determine customer loyalty. Theoretically, this study enhances the understanding of the multi-dimensional impact of value on customer loyalty, while managerially, it urges companies to emphasize economic benefits, strengthen co-creation, and communicate value effectively.